COVID-19 Vaccination Mandates and Vaccine Uptake - Alexander Karaivanov; Dongwoo Kim; Shih En Lu; Hitoshi Shigeoka (Institute of Labor Economics (IZA), 2021)
We evaluate the impact of government mandated proof of vaccination requirements for access to public venues and non-essential businesses on COVID-19 vaccine uptake. We find that the announcement of a mandate is associated with a rapid and significant surge in new vaccinations (more than 60% increase in weekly first doses) using the variation in the timing of these measures across Canadian provinces in a differencein-differences approach. Time-series analysis for each province and for France, Italy and Germany corroborates this finding, and we estimate cumulative gains of up to 5 percentage points in provincial vaccination rates and 790,000 or more first doses for Canada as a whole as of October 31, 2021 (5 to 13 weeks after the provincial mandate announcements). We also find large vaccination gains in France (3 to 5 mln first doses), Italy (around 6 mln) and Germany (around 3.5 mln) 11 to 16 weeks after the proof of vaccination mandate announcements.
Keywords: I18; I12; C23; 330; COVID-19; vaccine mandates; proof of vaccination; vaccine uptake; vaccine hesitancy; difference-in-differences; time-series analysis; counterfactuals